Perspective: challenges and research opportunities to enhance African Swine Fever control in the Philippines - Hsu, Chia-Hui; Schambow, Rachel A.; Humphreys, John; Montenegro, Maximino; Arzt, Jonathan; Perez, Andres M. (Frontiers in Veterinary Science, 2025)
African Swine Fever (ASF) is recognized as one of the most significant transboundary swine diseases due to its high mortality rate, rapid regional spread, and devastating economic consequences. Since its initial outbreak in July 2019, ASF has afflicted the Philippine swine industry for over 6 years. The implications of the epidemic extend beyond animal health, severely impacting the national pork supply chain and causing environmental concerns. In response, the Philippine government has implemented numerous policies for ASF management and control to support swine industry recovery. However, despite these substantial financial and logistical efforts, ASF remains prevalent, with frequent reemergence in many regions across the country. This perspective paper presents the outcomes of a collaborative workshop with the Philippine College of Swine Practitioners (PCSP), held in Batangas, Philippines, in November 2024. During this initiative, 40 local veterinary experts identified and ranked the most pressing challenges hindering current ASF control. Among the highest-ranked priorities were: (1) the role of intermediaries within the complex swine supply chain, (2) the inconsistent enforcement of guidelines across local government units, and (3) the underreporting of cases due to a lack of relevant local incentives. The resulting prioritizations offer valuable, field-level insights for refining national control strategies and hold significant relevance for neighboring countries facing similar struggles with ASF.